Correction: The association between the risk perceptions of COVID-19, trust in the government, political ideologies, and socio-demographic factors: A year-long cross-sectional study in South Korea. - Yo Han Lee; Hyun-Hee Heo; Hyerim Noh; Deok Hyun Jang; Young-Geun Choi; Won Mo Jang; Jin Yong Lee (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0280779.].